2017
DOI: 10.1590/s1806-92902017000700004
|View full text |Cite
|
Sign up to set email alerts
|

Cashew nut meal subjected to prolonged storage for quail feeding

Abstract: -The objective of this study was to evaluate the oxidative stability of cashew nut meal (CNM) at 180 days of storage and the effects of its use in the feed of meat quails. A total of 280 animals at seven days of age, of both sexes, were distributed in a completely randomized design with five treatments, in a 2 × 2 + 1 factorial arrangement, and seven replicates of eight birds each. The treatments were a control diet without CNM and diets containing levels of 12.5 or 25% of new CNM (NCNM) or stored for 180 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Braz et al (2017) did not observe any changes in the concentration of non protein sulfhydryl groups in the liver of laying hens fed diets containing CNSL, indicating no toxic effects of its compounds. Contrary to the observations in this study, López et al (2012) and Farias et al (2017) did not observe any changes in liver relative weight when feeding TCNSL to broilers and cashew nut meal to quails, respectively.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Braz et al (2017) did not observe any changes in the concentration of non protein sulfhydryl groups in the liver of laying hens fed diets containing CNSL, indicating no toxic effects of its compounds. Contrary to the observations in this study, López et al (2012) and Farias et al (2017) did not observe any changes in liver relative weight when feeding TCNSL to broilers and cashew nut meal to quails, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…In addition, some authors (Toyomizu et al, 2003;Murakami et al, 2014) evaluated CNSL as a natural anticoccidial and found a reduction of the severity of cecal lesions of chickens infected with coccidia, suggesting they act as ionophores. However, despite these positive effects, Farias et al (2017) did not observe any changes in the performance traits and gastrointestinal development of laying quails fed fresh or 180-d stored cashew nut meal.…”
Section: Introductionmentioning
confidence: 68%